Failure modes and buckling capacity of thin cylindrical reinforced cementitious shells under axial compression. (10th May 2018) - Koukouselis, Apostolos; Mistakidis, Euripidis
Highlights: The buckling behavior of an axially compressed cementitious cylinder is studied. The tolerance measurement proposed by EC3 seems to cover cementitious cylinders. The capacity curve for different imperfection amplitudes is numerically obtained. Three different failure modes are identified. The capacity curve is approximated by the same buckling parameters used by EC3. A simplified design approach similar to that of EC3 seems possible. Abstract: High performance cementitious composites have made possible the manufacturing of thin cementitious shell structures which are prone to buckling. Perhaps the most comprehensive design procedure for such shells is provided by the design recommendations issued by the International Association for Shells and Spatial Structures (IASS) which, however, are inconsistent with the modern European design framework. The scope of this paper is to contribute to the development of a design methodology similar to the one recommended by Eurocode 3 part 1–6, which is based on a capacity curve that represents all the possible failure states. In this respect, the capacity curve of an axially compressed cylinder is produced by geometrically and materially nonlinear analyses for different fabrication quality classes, which are in the sequel approximated by parametric capacity curves based on parameters determined following the concept of Eurocode 3.